2020
DOI: 10.21203/rs.3.rs-41983/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Long non-coding RNA H19 deficiency ameliorates bleomycin-induced pulmonary inflammation and fibrosis

Abstract: Background: The limited understanding of pathogenesis in idiopathic pulmonary fibrosis (IPF) impaired development of effective therapeutic strategies.The aim of this study was to investigate the role of long non-coding RNA H19 (lncRNA H19) in the progression of IPF. Methods: Bleomycin was used to induce pulmonary fibrosis in mice. The mRNAs and proteins expression in lung tissues with bleomycin-induced pulmonary fibrosis was determined by quantitative real-time polymerase chain reaction and western blot. H19 d… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…H19 downregulation alleviates fibroblast activation and lung fibrosis 77,78 . Wan et al 79 . further confirmed that H19 deficiency ameliorates bleomycin‐induced pulmonary infammation and fibrosis by using H19 knockout (H19−/−) mice generated by CRISPR/Cas9.…”
Section: Lncrna Directly Targets Non‐coding Genes To Regulate Pulmonamentioning
confidence: 91%
“…H19 downregulation alleviates fibroblast activation and lung fibrosis 77,78 . Wan et al 79 . further confirmed that H19 deficiency ameliorates bleomycin‐induced pulmonary infammation and fibrosis by using H19 knockout (H19−/−) mice generated by CRISPR/Cas9.…”
Section: Lncrna Directly Targets Non‐coding Genes To Regulate Pulmonamentioning
confidence: 91%